2019
DOI: 10.1111/1462-2920.14484
|View full text |Cite
|
Sign up to set email alerts
|

Elevated pCO2 alters marine heterotrophic bacterial community composition and metabolic potential in response to a pulse of phytoplankton organic matter

Abstract: Summary Factors that affect the respiration of organic carbon by marine bacteria can alter the extent to which the oceans act as a sink of atmospheric carbon dioxide. We designed seawater dilution experiments to assess the effect of pCO2 enrichment on heterotrophic bacterial community composition and metabolic potential in response to a pulse of phytoplankton‐derived organic carbon. Experiments included treatments of elevated (1000 p.p.m.) and low (250 p.p.m.) pCO2 amended with 10 μmol L−1 dissolved organic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 72 publications
(111 reference statements)
3
9
0
Order By: Relevance
“…The increase in the relative contribution of Alteromonadales lineages (specifically Marinobacter and Alteromonas) to total 16S rRNA amplicons was ubiquitous across the control, carryover, and copepod treatments. This shift has been observed in incubation studies before (e.g., Eilers et al, 2000;McCarren et al, 2010;Stewart et al, 2012;James et al, 2019) and appears to be a common bottle effect. The disconnect between only a slight increase in total cell counts and a substantial increase in relative contribution of Alteromonadales to total amplicons additionally likely reflect bias associated with multiple copies of the 16S rRNA gene (Klappenbach et al, 2000;Math et al, 2012;Větrovský and Baldrian, 2013).…”
Section: B10)supporting
confidence: 62%
See 1 more Smart Citation
“…The increase in the relative contribution of Alteromonadales lineages (specifically Marinobacter and Alteromonas) to total 16S rRNA amplicons was ubiquitous across the control, carryover, and copepod treatments. This shift has been observed in incubation studies before (e.g., Eilers et al, 2000;McCarren et al, 2010;Stewart et al, 2012;James et al, 2019) and appears to be a common bottle effect. The disconnect between only a slight increase in total cell counts and a substantial increase in relative contribution of Alteromonadales to total amplicons additionally likely reflect bias associated with multiple copies of the 16S rRNA gene (Klappenbach et al, 2000;Math et al, 2012;Větrovský and Baldrian, 2013).…”
Section: B10)supporting
confidence: 62%
“…By day 5, the bacterioplankton community structure in control and carryover treatments shifted from communities dominated by oligotrophs, described above, to communities where the relative contribution appears to be dominated by putative copiotrophs i.e., Alteromonas and Thiotrichales (Figure 6). The response by these representative Gammaproteobacteria is a bottle effect that has been observed previously in various incubation studies when trace amounts of labile organic matter is available (Eilers et al, 2000;McCarren et al, 2010;Stewart et al, 2012;James et al, 2019). While we did observe an increase in Alteromonas in all treatments, the main point is that the responding bacterioplankton community in the zooplankton excreta enriched treatment was significantly different from the responding community observed in the control and carryover treatments.…”
Section: Microbial Remineralization Experimentssupporting
confidence: 54%
“…With incubation time, communities composed of diverse oligotrophs and archaea at T0 (accounting for an average relative abundance of 67%) all shifted to communities mostly dominated by copiotrophs at TF (accounting for an average relative abundance of 80%) in all treatments including unamended controls. Alteromonadaceae especially dominated in all treatments at TF (Figure 6, left panel), a common observation reported in other studies as possibly being due to bottle effects (Eilers et al, 2000;McCarren et al, 2010;Stewart et al, 2012;James et al, 2019). To avoid skewing of community structure by this dominant taxon, we standardized the relative abundance of each family (z-score; Figure 6, right panel).…”
Section: Unfractionated Microbial Community Structurementioning
confidence: 67%
“…DOM released from phytoplankton consists of a myriad of compounds that span a range of turnover times and biological reactivity from labile to recalcitrant (Carlson, 2002;Hansell, 2013;Carlson and Hansell, 2015). A number of studies have demonstrated that the rate, efficiency, and composition of bacterioplankton growth is sensitive to the source of phytoplankton DOM, including effects of phytoplankton community structure (Pinhassi and Berman, 2003;Teeling et al, 2012), phytoplankton bloom dynamics (Wear et al, 2015), ocean acidification (James et al, 2019) and nutrient regime (Goldberg et al, 2017). Identifying how components of the DOM pool released by phytoplankton are incorporated by different bacterioplankton taxa is central to understanding both the dynamics of DOM globally and the factors maintaining the tremendous diversity of heterotrophic bacterioplankton in the world's oceans.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial respiration (BR) accounts for 50-90% of community respiration (CR) (Biddanda and Cotner, 2002). Ocean acidification is reported to modulate the cell morphology (Yu and Chen, 2019), metabolism (Westwood et al, 2018;Vaque et al, 2019), and community structure (Grossart et al, 2006;James et al, 2019) of marine bacteria, ultimately affecting the carbon flow of the marine microbial loop. Although the effect of ocean acidification on bacterial metabolic activity and community composition has been recognized in the last decades (Riebesell and Gattuso, 2015), contrasting findings are achieved (Weinbauer et al, 2011), likely due to different nutritional conditions or experimental designs.…”
Section: Introductionmentioning
confidence: 99%